Integrating psychological assessment in achalasia management: addressing mental health to enhance patient outcomes - Mohsen Khosravi; Ahoora Kavoosi; Rafat Rezapour-Nasrabad; Melody Omraninava; Alireza Nazari Anamagh; Seyed Teymur Seyedi Asl (PAGEPress Publications, 2024)
Achalasia is a chronic esophageal disorder with a generally favorable prognosis; however, approximately 20% of patients experience persistent or recurrent symptoms despite therapeutic interventions. These ongoing symptoms can significantly diminish both disease-specific and overall quality of life. Although the physical manifestations of achalasia, such as regurgitation, dysphagia, chest pain, and weight loss, are well-documented and assessed using the Eckardt score, the psychological burden of the disease remains underexplored. Individuals with achalasia are at an increased risk of mental health issues, including depression, anxiety, and somatization, exacerbated by the emotional strain and social limitations imposed by the disease. Despite this, psychological impacts are often overlooked in clinical settings, leading to inadequate mental health support for these patients. This article underscores the necessity for prompt psychological assessments during the diagnosis of achalasia to better address these mental health challenges and improve overall patient care.